2019
DOI: 10.1111/srt.12754
|View full text |Cite
|
Sign up to set email alerts
|

A novel in vivo test method for evaluating the infrared radiation protection provided by sunscreen products

Abstract: Background Infrared radiation (IR) exposure generates reactive oxygen species and induces matrix metalloproteinase‐1 expression in human skin. Moreover, while not as acute as ultraviolet radiation, repeated infrared irradiation can result in the photoaging of skin. Broad‐spectrum sunscreens can protect skin from IR, but no human in vivo test methods for the evaluation of sunscreens' IR protection effect have been developed. We aimed to develop such a method. Materials and Methods We included 155 Korean subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Originally, we performed a set of clinical evaluation method using a commercially available IR spectrometer that is used for mineral exploration in the field of geology. 38 Based on our previous research, measurement of the skin reflectance in the IR-A region was found to be not affected by the skin color or moisture content. However, the intensity of the light source employed for that study was approximately seven times higher than that of the IR-A in actual sunlight due to the fact it was not possible to control the intensity of our fabricated Ir device; this result in discomfort for the test subjects.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Originally, we performed a set of clinical evaluation method using a commercially available IR spectrometer that is used for mineral exploration in the field of geology. 38 Based on our previous research, measurement of the skin reflectance in the IR-A region was found to be not affected by the skin color or moisture content. However, the intensity of the light source employed for that study was approximately seven times higher than that of the IR-A in actual sunlight due to the fact it was not possible to control the intensity of our fabricated Ir device; this result in discomfort for the test subjects.…”
Section: Discussionmentioning
confidence: 93%
“…In our previous study, we developed an in vivo determination method for the IR-A protection factor on human skin. 38 However, the intensity of IR-A in the used device was too high to mimic actual IR-A irradiating human skin on the Earth's surface. In addition, the intensity of IR-A irradiating the Earth's surface changes with the season and location, and so it is necessary to obtain information regarding the IR-A intensity, such as an annual average or maximum.…”
Section: Monitoring Of the Daily Ir-a Intensity In Sunlightmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the IR protection effectiveness of sunscreen has been investigated through the in vivo method. Kim et al (2019) evaluated the resistance to IR rays provided by sunscreen in 155 Korean volunteers, and recorded the IR reflectance of volunteer's skin using a benchtop model of an IR light source and a reflectance measuring probe [87]. The results showed that the infrared protection factor (IPF) in protected skin was greater than that of unprotected skin.…”
Section: Sunscreen Against Thermal Irmentioning
confidence: 99%